2019
DOI: 10.1007/s13167-019-00175-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of clinical trait–related lncRNA and mRNA biomarkers with weighted gene co-expression network analysis as useful tool for personalized medicine in ovarian cancer

Abstract: Relevance The pathogenesis and biomarkers of ovarian cancer (OC) remain not well-known in diagnosis, effective therapy, and prognostic assessment in OC personalized medicine. The novel identified lncRNA and mRNA biomarkers from gene co-expression modules associated with clinical traits provide new insight for effective treatment of ovarian cancer. Purpose Long non-coding RNAs (lncRNAs) are relevant to tumorigenesis via multiple mechanisms. This study aimed to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
86
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(91 citation statements)
references
References 39 publications
0
86
0
Order By: Relevance
“…Therefore, the repression of HOTAIRM1 may affect miRNAs other than miR-107. A previous study to identify prognosis-related lncRNAs in ovarian cancer tissues, showed that HOTAIRM1 regulates hub genes through several miRNAs, including miR-107, miR-103a-3p, miR-129-5p, miR-152-3p, miR-148a-3p, and miR-148b-3p 32 . In vitro and in vivo studies demonstrated that HOTAIRM1 may play a negative role in the development of head and neck tumors through the HOTAIRM1/microRNA-148a axis 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the repression of HOTAIRM1 may affect miRNAs other than miR-107. A previous study to identify prognosis-related lncRNAs in ovarian cancer tissues, showed that HOTAIRM1 regulates hub genes through several miRNAs, including miR-107, miR-103a-3p, miR-129-5p, miR-152-3p, miR-148a-3p, and miR-148b-3p 32 . In vitro and in vivo studies demonstrated that HOTAIRM1 may play a negative role in the development of head and neck tumors through the HOTAIRM1/microRNA-148a axis 9 .…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of OCs based on those common biomarkers is still unsatisfactory. To accelerates predictive, preventive, and personalized medicine (PPPM) practice allowing prediction of response with substantially increased accuracy, various omics technologies, including transcriptome and proteome, have been tried [47][48][49].…”
Section: Limitations Clinical Meaning and Future Directionmentioning
confidence: 99%
“…OTUD6B-AS1 is transcribed from the opposite strand of the OTUD6B gene, which is located on chromosome 8 in head-to-head orientation to OTUD6BAS1 [26]. It was reported that high OTUD6B-AS1 expression indicates poor prognosis in ovarian cancer [27]. However, Gang Wang et al [28] found that high OTUD6B-AS1 expression was associated with improved survival and inhibited clear cell renal cell carcinoma proliferation via the Wnt/β-catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%